Analysis of newly detected tetracycline resistance genes and their flanking sequences in human intestinal bifidobacteria - Na Wang (Nature Portfolio, 2017)
Abstract Due to tetracycline abuse, the safe bifidobacteria in the human gastrointestinal intestinal tract (GIT) may serve as a reservoir of tetracycline resistance genes. In the present investigation of 92 bifidobacterial strains originating from the human GIT, tetracycline resistance in 29 strains was mediated by the tet(W), tet(O) or tet(S) gene, and this is the first report of tet(O)- and tet(S)-mediated tetracycline resistance in bifidobacteria. Antibiotic resistance genes harbored by bifidobacteria are transferred from other bacteria. However, the characteristics of the spread and integration of tetracycline resistance genes into the human intestinal bifidobacteria chromosome are poorly understood. Here, conserved sequences were identified in bifidobacterial strains positive for tet(W), tet(O), or tet(S), including the tet(W), tet(O), or tet(S) and their partial flanking sequences, which exhibited identity with the sequences in multiple human intestinal pathogens, and genes encoding 23 S rRNA, an ATP transporter, a Cpp protein, and a membrane-spanning protein were flanking by the 1920-bp tet(W), 1920-bp tet(O), 1800-bp tet(O) and 252-bp tet(S) in bifidobacteria, respectively. These findings suggest that tetracycline resistance genes harbored by human intestinal bifidobacteria might initially be transferred from pathogens and that each kind of tetracycline resistance gene might tend to insert in the vicinity of specific bifidobacteria genes.